AUTOMATIC SOLAR TRACKING SYSTEM - Parasnis N. V.; Tadamalle A. P (International Journal of Innovations in Engineering Research and Technology, 2021)
The solar energy is a clean, freely and abundantly available alternative energy source in nature. Capturing solar energy from nature is an advantageous task for power generation. Conversion of sun energy into another form is a highly complex phenomenon. For this purpose, Photo-Voltaic (PV) panels are used which convert Sun energy to Direct Current (DC) electrical energy. Conventional fixed type PV panels extract maximum energy only during 12 noon to 2 PM which results in less efficiency. Therefore, building of an automatic solar tracking system is the need of an hour. PV panels have to be perpendicular with the sun for maximum energy extraction which can be fulfilled by automatic tracking. This project includes the design and development of microcontroller based automatic solar tracking system.